Methods engineering study on Mcgraw Engineering - Abanto, Ray Anthony; Poblete, Natalie Ian D.; Resoso, Michael; Villanueva, Racquel D. (College of Engineering, 2002)
McGraw Engineering is a manufacturing company whose major product line in manufacturing consists of dry-type transformers, oil-immersed self-cooled, substation and distribution transformers. The study is centered on methods improvement since the manufacturing of these types is highly competitive, especially in the vicinity of the production site. Methods documentation and analysis is done on actual plant visits, employing various tools learned in the Methods Engineering class. The study addressed problems, namely: *Improper attire *No definite work schedule *Inconsistent supervision *No incentive plan *Inefficient layout of machines *No standard operating procedures. It is the task of the group to come up with possible solutions to the aforementioned problems. The group came up with at least two possible solutions or alternatives for each problem. Each alternative is weighed against specific criteria for each problem, and then assessed of risks and threats against the existing conditions. The alternatives that are ?GO? in each want objective and have threats that are more desirable are chosen. The chosen alternatives are subjects for implementation. The group is also tasked to at least try to plan the implementation of the chosen alternatives. In doing so, the group came up with an implementation plan and an implementation strategy. These plans are guides for the Subject Company so that they may be able to implement the various changes brought about by the alternatives. Application of the tools learned in the methods analysis class is very much of use in this project study. The group would not be able to come up with all that is inside this paper without the thorough understanding of the various tools of Methods Engineering.